A case of brain abscess thought to be caused by dental infection with Streptococcus intermedius and discussion of the literature. Issue 4 (July 2022) - Yoneyama, Yuya; Matsuno, Tomonori; Fujioka-Kobayashi, Masako; Hasegawa, On; Chikazu, Daichi; Satomi, Takafumi
Abstract: Brain abscesses are mainly caused by pyogenic bacteria such as staphylococci and streptococci. The oral bacteria Streptococcus intermedius, which has attracted attention in recent years because of its pathogenicity and tendency to cause infections in the central nervous system, is remotely transferred. We report a case of a brain abscess caused by hematogenous infection by oral bacteria. A 64-year-old man presented to an emergency hospital with a chief complaint of headache and was diagnosed with a brain abscess. He underwent surgery to drain the abscess under general anesthesia. Oral bacteria were detected in the abscess, and his oral hygiene was managed in our department. It is common for oral surgeons to examine patients with abscesses in other organs to investigate the secondary source of infection. In the secondary investigation, it is often difficult to identify the bacteria, even after oral bacteriological examination, because of the passage of time or because antimicrobial agents have been administered. In this study, we describe a case of a brain abscess caused by an anti-TNFα antibody drug administered for the treatment of Behçet's disease, which increased the patient's susceptibility to an infection thought to be of dental origin.